P-o-c-n hybrid intumescent flame retardant material and preparation method thereof
Patent Information
- Application Number
- CN202611291967.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-08-25
AI Technical Summary
Existing flame-retardant epoxy composite materials for rail transit are prone to flame retardant migration and loss during long-term use, which cannot meet the 15-year long-term protection requirements of high-speed rail. In addition, traditional materials have poor flame-retardant effect during combustion.
Using POCN hybrid intumescent flame retardant material, the flame retardant is constructed through stepwise graft copolymerization reaction, forming a triple function of acid source, gas source and char source. It achieves dual flame retardancy of gas phase and condensed phase at high temperature. By utilizing the chemical bonding of phosphorus source, nitrogen source and acid source, a dense and stable char layer is formed, and synergistic additives such as graphene and montmorillonite are added to improve the density and mechanical properties of the char layer.
It achieves long-lasting and high-efficiency flame retardants. The flame retardants do not easily migrate at high temperatures, forming a dense carbon layer to block heat and oxygen transfer, thereby improving the flame retardant rating and mechanical properties of the material and meeting the long-term use requirements of high-speed rail.
Smart Images

Figure CN122790384B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material technology, and in particular to a POCN hybrid intumescent flame retardant material and its preparation method. Background Technology
[0002] Currently, human travel is inseparable from transportation, and rail transit is an important component in order to increase the safety of transportation. When selecting materials for the manufacture of rail transit vehicles, flame-retardant composite materials with flame-retardant properties are often used.
[0003] The current flame-retardant epoxy composite materials and supporting molding processes used in rail transit cannot meet the comprehensive requirements of interior panels. The specific defects are as follows: lack of flame retardant migration and long-term effectiveness: traditional PN flame retardants are generally physically mixed with the matrix, and the retention rate after Soxhlet extraction is less than 60% after 24 hours. The flame retardant rating is downgraded after 1000 hours of service. During combustion, the flame retardant is also easily lost with the smoke, which cannot meet the 15-year long-term protection requirements of high-speed rail.
[0004] Therefore, in order to address the above problems, there is an urgent need for a flame-retardant material with good flame-retardant effect and long protection time. Summary of the Invention
[0005] This invention provides a POCN hybrid intumescent flame retardant material and its preparation method, which can provide a flame retardant material with good flame retardant effect and long protection time.
[0006] In a first aspect, embodiments of the present invention provide a method for preparing a POCN hybrid intumescent flame-retardant material, comprising: S1, a flame retardant is prepared by using a phosphorus source containing phosphorus, a nitrogen source containing nitrogen, and an acid source containing polyphosphate groups; S2, the flame retardant and resin matrix are mixed and cured to obtain a flame retardant material; S1 includes: S101, a phosphorus source and a material including epoxy groups are mixed and reacted to obtain a phosphorus-carbon reactant containing POC chains; S102, the phosphorus-carbon reactant and the acid source are mixed, and a hybrid mixture is obtained after the reaction; S103, the hybrid mixture is mixed with a nitrogen source, and a flame retardant is obtained after the reaction; The reaction temperature in S101 is 70~80℃ and the reaction time is 1.5~2.5h; the reaction temperature in S102 is 85~95℃ and the reaction time is 2.5~3.5h; and the reaction temperature in S103 is 80~90℃ and the reaction time is 2.0~3.0h.
[0007] Optionally, in S1, the phosphorus source includes at least one DOPO derivative, which includes at least one of DOPO-OH, DOPO-MA, and DOPO-EP.
[0008] Optionally, in S1, the nitrogen source includes at least one of melamine-formaldehyde resin, melamine cyanurate, and dicyandiamide.
[0009] Optionally, in S1, the acid source includes at least one of polyphosphate, ammonium polyphosphate, and pentaerythritol phosphate.
[0010] Optionally, S2 includes: The flame retardant, synergist, and resin matrix are mixed and cured to obtain a flame retardant material; wherein the synergist includes at least one of graphene-based additives, hybrid montmorillonite, microencapsulated hydroxide, and hexagonal boron nitride.
[0011] Optionally, the mass fractions of each substance in S2 are: 8-14 parts of the flame retardant, 0.6-1.3 parts of the graphene additive, 2-4 parts of the hybrid montmorillonite, 1.7-2.3 parts of the microencapsulated hydroxide, and 90-140 parts of the resin matrix.
[0012] Optionally, before S2, the following also includes: Select at least one fiber; the type of fiber includes at least one of basalt fiber, carbon fiber and glass fiber; The selected fibers were grafted and modified to obtain modified fibers. S2 includes: S201, the flame retardant and the resin matrix are mixed to obtain a mixed adhesive solution; S202, the modified fiber is impregnated with the mixed adhesive and cured to obtain a flame-retardant material.
[0013] Optionally, before S202, the modified fiber is pre-compressed; S202 includes: The modified fiber is first dipped in a low-concentration mixed adhesive solution of 8-10 parts flame retardant / 100 parts resin matrix, drained, and then dipped in a high-concentration mixed adhesive solution of 11-13 parts flame retardant / 100 parts resin matrix. The modified fibers impregnated with the mixed adhesive solution are subjected to gradient curing.
[0014] Optionally, the pre-compression molding is carried out at 0.3~0.5MPa and 25~40℃.
[0015] Optionally, the gradient curing heating rate is 3~6℃ / min, the holding temperatures are 100~110℃, 130~140℃ and 150~160℃ respectively, and the curing pressure is 0.7~0.9MPa.
[0016] Optionally, S2 includes: The flame retardant, resin matrix, curing agent and toughening agent are mixed and cured to obtain a flame retardant material; wherein the resin matrix includes at least one epoxy resin.
[0017] Secondly, embodiments of the present invention also provide a POCN hybrid intumescent flame retardant material, prepared according to any of the preparation methods described in the above embodiments.
[0018] Compared with the prior art, the present invention has at least the following beneficial effects: The flame retardant is constructed from phosphorus, nitrogen, and acid sources. As the core flame-retardant functional phase of the composite material, the flame retardant plays a triple role as an acid source, gas source, and char source. Specifically, it achieves dual flame retardancy in both the gas and condensed phases at high temperatures; in the gas phase, it decomposes and releases free radical quenchers such as PO•, terminating the combustion chain reaction; in the condensed phase, it achieves uniform expansion and char formation through the synergistic effect of the acid and gas sources, forming a dense and stable char layer that blocks heat and oxygen transfer. At the same time, it solves the problem of easy migration and loss of traditional flame retardants due to physical mixing, thus improving the long-term flame retardancy. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 This is a flowchart of a method for preparing a POCN hybrid intumescent flame retardant material provided by the present invention. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0022] Please refer to Figure 1This invention provides a method for preparing a POCN hybrid intumescent flame retardant material, comprising: S1, a flame retardant is prepared by using a phosphorus source containing phosphorus, a nitrogen source containing nitrogen, and an acid source containing polyphosphate groups; S2, the flame retardant and resin matrix are mixed and cured to obtain a flame retardant material.
[0023] In this invention, the flame retardant is constructed from phosphorus, nitrogen, and acid sources, serving as the core flame-retardant functional phase of the composite material. The flame retardant functions as an acid source, gas source, and char source. At high temperatures, it achieves dual flame retardancy in both the gas and condensed phases. In the gas phase, it decomposes and releases free radical quenchers such as PO•, terminating the combustion chain reaction. In the condensed phase, the acid and gas sources work together to achieve uniform expansion and char formation, creating a dense and stable char layer that blocks heat and oxygen transfer. This also solves the problem of easy migration and loss during physical mixing of traditional flame retardants, improving the long-lasting flame retardant effect.
[0024] Specifically, this flame retardant is a single component that functions as an acid source, gas source, and carbon source. At high temperatures, the acid source, such as polyphosphate, decomposes to generate polyphosphoric acid, which catalytically dehydrates and carbonizes the carbon source in the composite material, forming an initial carbon layer. The gas source, melamine resin, decomposes to release inert gases such as NH3 and N2, causing the initial carbon layer to expand uniformly and form a porous expanded carbon layer. The phosphorus source, DOPO derivatives, forms POC hybrid chains that generate a stable phosphorus-oxygen ceramic phase on the surface of the carbon layer, coating the carbon layer and improving its high-temperature oxidation resistance. At the same time, each component participates in the carbonization reaction, increasing the carbon content and structural stability of the carbon layer, ultimately forming an expanded carbon layer with uniform thickness, high density, and strong anti-collapse properties, achieving efficient heat insulation and flame retardancy in the condensed phase. The PO• free radicals released by the decomposition of DOPO derivatives in the gas phase can quickly capture hydroxyl and hydrogen free radicals during combustion, terminating the combustion chain reaction and achieving gas phase flame retardancy, ultimately achieving a dual flame retardant synergistic effect between the gas phase and the condensed phase.
[0025] In some embodiments of the present invention, in S1, the phosphorus source includes at least one DOPO derivative, which includes at least one of DOPO-OH, DOPO-MA and DOPO-EP; The nitrogen source includes at least one of melamine-formaldehyde resin, melamine cyanurate, and dicyandiamide; The acid source includes at least one of polyphosphate, ammonium polyphosphate, and pentaerythritol phosphate.
[0026] In some embodiments of the present invention, S1 includes: S101, a phosphorus source and a material including epoxy groups are mixed and reacted to obtain a phosphorus-carbon reactant containing POC chains; S102, the phosphorus-carbon reactant and the acid source are mixed to obtain a hybrid mixture; S103, the hybrid mixture is mixed with a nitrogen source to obtain a flame retardant.
[0027] In this embodiment, DOPO derivatives (phosphorus source / carbon source), melamine resins (nitrogen source / gas source), and polyphosphate esters (acid source) are molecularly fused through stepwise grafting and copolymerization reactions to construct a hybrid intumescent flame retardant containing POCN covalent chains. This achieves chemical bonding and dispersion of phosphorus, nitrogen, oxygen, and carbon elements, fundamentally solving the problems of easy migration and low Soxhlet extraction retention rate in traditional phosphorus-nitrogen flame retardants, thus ensuring the 15-year long-term service requirements of high-speed rail.
[0028] In some embodiments of the present invention, the reaction temperature in S101 is 70~80℃ and the reaction time is 1.5~2.5h, the reaction temperature in S102 is 85~95℃ and the reaction time is 2.5~3.5h, and the reaction temperature in S103 is 80~90℃ and the reaction time is 2.0~3.0h.
[0029] In some embodiments of the present invention, S2 includes: The flame retardant, synergist, and resin matrix are mixed and cured to obtain a flame retardant material; wherein the synergist includes at least one of graphene-based additives (such as graphene quantum dots, graphene oxide, etc.), hybrid montmorillonite, microencapsulated hydroxide, and hexagonal boron nitride.
[0030] In this embodiment, one or more of the following additives can be selected and combined: graphene quantum dots, graphene oxide, hybrid montmorillonite, microcapsule magnesium hydroxide, microcapsule aluminum hydroxide, and hexagonal boron nitride (h-BN). These synergistic additives can fill the micropores of the expanded carbon layer, improving its density and thermal insulation performance. Graphene-based additives can also construct a thermally conductive network, achieving a functional adaptation between heat dissipation during normal service and fire insulation, while simultaneously adsorbing smoke particles and flame-retardant decomposition products, reducing smoke density and the release of toxic gases. Montmorillonite and microcapsule metal hydroxides can further enhance flame-retardant efficiency, regulate the char formation rate and carbon layer structural stability, and further optimize the safety performance of the composite material.
[0031] It should be noted that graphene-based additives and hybrid montmorillonite can be introduced simultaneously as synergistic additives. In this way, by utilizing the high specific surface area, high thermal conductivity, and layered structure characteristics of graphene quantum dots, a continuous thermally conductive network can be constructed in the epoxy matrix. This allows the composite material to quickly dissipate heat during normal service, avoiding matrix degradation and premature decomposition of flame retardants caused by local overheating, thus meeting the heat dissipation requirements of high-speed rail roofs. During combustion, the layered structure of graphene quantum dots can be interspersed in the char layer, improving the mechanical strength of the char layer, while adsorbing smoke particles and flame retardant decomposition products, reducing smoke density and the release of toxic gases, and improving safety performance. After intercalation modification, hybrid montmorillonite exhibits increased interlayer spacing and can be exfoliated into nanosheets within the matrix. During combustion, these montmorillonite sheets rapidly migrate to the surface and interior of the char layer, filling micropores, gaps, and defects, reducing porosity, and improving density and thermal insulation performance. Simultaneously, the inorganic sheet structure of montmorillonite possesses excellent high-temperature stability, further enhancing the high-temperature collapse resistance and oxidation resistance of the char layer. The synergistic effect of graphene and montmorillonite achieves a multi-functional adaptation of the expanded char layer, including long service life, high heat dissipation, flame retardancy, thermal insulation, and smoke suppression and detoxification, perfectly meeting the differentiated performance requirements of high-speed rail interior panels.
[0032] In some embodiments of the present invention, the mass fractions of each substance in S2 are: 8-14 parts of the flame retardant, 0.6-1.3 parts of the graphene additive, 2-4 parts of the hybrid montmorillonite, 1.7-2.3 parts of the microencapsulated hydroxide, and 90-140 parts of the resin matrix.
[0033] It should be noted that the content of the above-mentioned synergistic additives can be appropriately adjusted to meet the usage requirements of different high-speed rail components. Alternatively, a small amount of other functional synergistic additives can be added according to the needs of the high-speed rail components.
[0034] In some embodiments of the present invention, before S2, the following is also included: Select at least one fiber; the type of fiber includes at least one of basalt fiber, carbon fiber and glass fiber; The selected fibers were grafted and modified to obtain modified fibers after the reaction. S2 includes: S201, The flame retardant and the resin matrix are mixed and reacted to obtain a mixed adhesive solution; S202, the modified fiber is impregnated with the mixed adhesive and cured to obtain a flame-retardant material.
[0035] In this embodiment, the reinforcing fiber can be selected from two or more of the following: basalt fiber, carbon fiber (such as T300, T700, T800 grade), and glass fiber. The modifier used for fiber grafting modification can be one or more of the following: silane coupling agents KH550, KH560, and KH570.
[0036] In this embodiment, fibers are selected as the mechanical load-bearing skeleton of the composite material to improve tensile strength, low-temperature impact strength and weather resistance, and to meet the structural load-bearing requirements of high-speed rail interior panels. After modification, the fibers can form covalent interconnections with the matrix and flame retardant, and are uniformly interwoven in the expanded carbon layer to form a physical skeleton, which inhibits the high-temperature collapse of the carbon layer. At the same time, the carbon layer can coat the fibers to avoid high-temperature oxidation, thereby achieving a synergistic improvement in mechanical and flame-retardant properties.
[0037] Specifically, the hybrid fibers undergo acid etching pretreatment followed by silane coupling agent grafting modification. Acid etching introduces active groups such as hydroxyl and carboxyl groups onto the fiber surface, while grafting further introduces reactive groups such as amino and epoxy groups. Simultaneously, the POCN hybrid flame retardant undergoes end-group modification, introducing hydroxyl and carboxyl active groups. This allows the terminal active groups of the flame retardant to undergo directional chemical reactions with the amino / epoxy groups on the fiber surface and the epoxy groups in the matrix, forming covalent bonds and constructing a three-dimensional covalent interconnected network of "hybrid fiber-flame retardant-epoxy matrix," significantly improving the interfacial bonding strength.
[0038] Performance Synergy Mechanism: Interfacial covalent interconnection enables stress to be uniformly transferred among components, avoiding stress concentration caused by filler and fiber agglomeration. This significantly improves the tensile strength, low-temperature impact strength, and interfacial shear strength of the composite material, solving the problem of a significant decrease in mechanical properties caused by adding a large amount of flame retardant in traditional systems. At the same time, basalt / carbon fiber is uniformly interwoven in the expanded carbon layer in a three-dimensional network structure, forming a rigid physical skeleton that restricts the shrinkage, cracking, and collapse of the carbon layer at high temperatures, improving the structural stability of the carbon layer. The dense carbon layer formed at high temperatures can tightly coat the fiber surface, isolating oxygen and high temperature, preventing the fiber from being oxidized and degraded, and improving the high-temperature mechanical retention rate of the composite material. Ultimately, this achieves a synergistic effect of mechanical flame retardancy without mutual damage.
[0039] In some embodiments of the present invention, before S202, the modified fiber is pre-compressed at 0.3~0.5MPa and 25~40°C. S202 includes: The modified fiber was first dipped in a low-concentration mixed adhesive solution of 8 parts flame retardant / 100 parts resin matrix, drained, and then dipped in a high-concentration mixed adhesive solution of 11 parts flame retardant / 100 parts resin matrix. The modified fibers impregnated with the mixed adhesive are subjected to gradient curing. The heating rate of the gradient curing is 3~6℃ / min, the holding temperatures are 100~110℃, 130~140℃ and 150~160℃ respectively, and the curing pressure is 0.7~0.9MPa.
[0040] In this embodiment, the molding process breaks through the limitations of traditional generalized molding processes. It can design customized pre-forming methods and gradient curing parameters according to the different performance and molding requirements of high-speed rail side wall panels (curved surface molding), roof panels (thermal conduction-thermal insulation synergy), and seat back panels (impact resistance-wear resistance) in combination with the formation law of expanded carbon layers, so as to achieve precise matching between material molding and carbon layer formation.
[0041] Specifically, in the preforming stage, various methods such as silicone mold pre-pressing, unidirectional layup cold pressing, and hollow mold pre-pressing are used according to the component requirements to control the fiber layup direction, resin impregnation effect, and preform density, precisely controlling the resin content to 53-56%, laying the foundation for subsequent gradient curing and char layer formation. In the gradient curing stage, a curing method of "multi-stage heating + constant temperature and pressure" is adopted to precisely control the curing rate and matrix cross-linking degree, ensuring that the resin matrix is fully cross-linked while matching the formation rhythm of the expandable char layer of "catalytic carbonization - uniform expansion - ceramic coating", avoiding structural defects such as loose char layer, cracking, and collapse caused by excessively fast / slow curing rates. At the same time, according to the mechanical and flame retardant requirements of different components, the curing temperature, holding time, and curing pressure are adjusted individually to achieve precise adaptation of the performance of each component.
[0042] This process not only significantly improves the molding yield of high-speed rail interior panels and reduces cracking rate and batch performance fluctuations, but also optimizes process steps, shortens production cycle, and reduces industrial-scale production costs.
[0043] It should be noted that if the component is a top plate that does not require large surface deformation, the modified fibers and the mixed adhesive can be mixed by pre-impregnation before the pre-pressing process.
[0044] In some embodiments of the present invention, the flame retardant, resin matrix, curing agent and toughening agent are mixed and cured to obtain a flame retardant material; wherein the resin matrix includes at least one epoxy resin.
[0045] In this embodiment, bisphenol A type epoxy resin (such as E51, E44, E54) or bisphenol F type epoxy resin, or a combination of both, are preferred, along with curing agents 4,4'-diaminodiphenyl sulfone (DDS) or methyltetrahydrophthalic anhydride. Toughening agents can be carboxyl-terminated butadiene-acrylonitrile rubber (CTBN), hydroxyl-terminated butadiene-acrylonitrile rubber (HTBN), or polyethersulfone (PES). Serving as the crosslinking skeleton and carbon source of the composite material, it provides a bonding matrix for each component. By combining different epoxy resins and adding toughening agents, the brittleness of the material is reduced, and its flexural formability is improved, adapting to the molding requirements of high-speed rail curved interior panels. Simultaneously, active groups can be introduced through graft modification to form covalent bonds with flame retardants and hybrid fibers, constructing a fully interconnected network and enhancing interfacial bonding strength.
[0046] It should be noted that the number of copies in this application refers to the number of mass copies.
[0047] This invention also provides a POCN hybrid intumescent flame retardant material, prepared according to any of the preparation methods described in the above embodiments.
[0048] To more clearly illustrate the technical solution and advantages of the present invention, the following describes the solution of this application in detail through several embodiments.
[0049] Example 1: High-speed rail side wall panel (1) The raw material components and addition amounts are shown in Table 1. Table 1
[0050] (2) Preparation process
[0051] Hybrid fiber pretreatment: Basalt fiber and carbon fiber were mixed at a volume ratio of 3:1 and etched in a H2SO4 / H2O2 mixture (volume ratio 3:1) at 80℃ for 2 hours. The mixture was washed with deionized water until neutral and then vacuum dried at 60℃ for 4 hours. A KH550 / KH560 (mass ratio 1:1.2) ethanol-deionized water mixed solution (silane mass fraction 5%) was prepared. The pH of the system was adjusted to 4.5~5.0 using glacial acetic acid, and the mixture was stirred at room temperature for 30 minutes for pre-hydrolysis. The pretreated fiber was then immersed in the pre-hydrolysis solution and grafted at a constant temperature of 65℃ for 3 hours. After filtration, the fiber was vacuum dried at 80℃ for 6 hours to obtain bissilane grafted hybrid fiber. Flame retardant preparation: ① Add 5 parts DOPO-OH and 3 parts glycidol to a reaction vessel and mechanically stir at 75℃ for 2 hours (400 r / min) to form POC chains; ② Add 4 parts polyphosphate ester and heat to 90℃ for 3 hours; ③ Add 2 parts melamine-formaldehyde resin and keep at 85℃ for 2.5 hours; ④ Centrifuge (10000 r / min, 15 min), wash 3 times with ethanol, and vacuum dry at 80℃ for 6 hours to obtain POCN hybrid intumescent flame retardant; Functional phase dispersion: 11 parts flame retardant, 3 parts hybrid montmorillonite, 0.9 parts graphene quantum dots and 2 parts microcapsule magnesium hydroxide were added to 40 parts acetone and ultrasonically dispersed at 700W for 30 minutes to form a uniform dispersion. Matrix preparation: Mix 80 parts of E51 and 20 parts of bisphenol F epoxy resin and heat to 80°C. Add the above dispersion, 32 parts of DDS (4,4'-diaminodiphenyl sulfone), and 2.5 parts of CTBN (carboxyl-terminated nitrile butadiene rubber). Stir mechanically for 1 hour (500 r / min), and degas under vacuum for 30 minutes (vacuum degree -0.095 MPa). Control the rubber content to 55%. Preforming and dip coating: The mixed fibers are laid into a silicone mold and pre-pressed at 0.3 MPa and 30°C for 1 hour; then a gradient dip coating process is adopted, first dipped in a low concentration mixed adhesive solution (8 parts flame retardant / 100 parts matrix) for 10 minutes, drained and then dipped in a high concentration mixed adhesive solution (11 parts flame retardant / 100 parts matrix) for 15 minutes. Gradient curing: The mold is placed in an autoclave and cured according to the following procedure: 100℃ for 1.5h → heating rate 5℃ / min to 130℃ → holding for 2h → heating rate 5℃ / min to 160℃ → holding for 2.5h, curing pressure 0.8MPa, and then naturally cooled to room temperature. Post-processing: After demolding, the edges are trimmed with a laser trimming machine to obtain the finished high-speed rail side wall panel (size: 2400mm×1200mm×8mm).
[0052] (3) Performance test results are shown in Table 2 Table 2 The above examples demonstrate that the material of the present invention forms carbon through the synergistic acid-gas source of the intumescent flame retardant, which not only meets the requirements for curved surface forming of the side wall panel, but also forms a dense carbon layer to achieve long-term protection. In addition, this example addresses the requirements for curved surface forming, flame retardancy, and mechanical load-bearing capacity of the high-speed rail side wall panel by preparing corresponding composite materials and adopting a customized molding process. The resulting side wall panel meets the standards of GB8624-2012 B1 level, TB / T3237-2010, and EN45545-2HL3 level, and is compatible with the curved surface installation requirements of the high-speed rail car body.
[0053] Example 2: High-speed rail roof (1) The raw material components and addition amounts are shown in Table 3. Table 3
[0054] (2) Preparation process
[0055] The same hybrid fiber pretreatment process as in Example 1; Flame retardant preparation: Same as the flame retardant preparation process in Example 1; Mixing and dispersing: Add 9 parts flame retardant, 2 parts hybrid montmorillonite, 0.6 parts graphene quantum dots, 1.5 parts microcapsule magnesium hydroxide and 5 parts hexagonal boron nitride to 35 parts acetone, and ultrasonically disperse at 750W for 35 minutes to form a uniform dispersion. Matrix preparation: Mix 80 parts of E51 and 20 parts of bisphenol F epoxy resin and heat to 80°C. Add the above dispersion, 30 parts of DDS, and 2 parts of CTBN. Stir mechanically for 1 hour (550 r / min), and degas under vacuum for 30 minutes (-0.095 MPa). The glue content is controlled at 54%. Preforming: The mixed fibers are laid up in a unidirectional manner (layup angle 0°), placed in a cold press, and cold-pressed at 0.5MPa and 25℃ for 0.5h to compact the fiber bundles; Gradient curing: The product is placed in an autoclave and cured according to the program (controlling the rate of expansion char formation): 110℃ for 2 hours → heating rate 5℃ / min to 140℃ → holding for 2.5 hours → heating rate 5℃ / min to 150℃ → holding for 2 hours, curing pressure 0.7MPa, and then naturally cooled to room temperature. Post-processing: After demolding, cut into standard top plate samples with dimensions of 3000mm×1500mm×6mm.
[0056] (3) Performance test results are shown in Table 4 Table 4 The above examples demonstrate that the present invention, through the synergistic effect of thermal conductive additives and regulated expandable carbon layers, enables the top plate to simultaneously achieve signal heat dissipation and fire insulation, with a flame retardant rating of V-0 that meets the GB8624-2012 B1 standard, thus resolving the functional conflict problem of traditional materials. Furthermore, it reduces the weight by 20% compared to traditional materials (2.06 g / cm³), meeting the service requirements of high-speed rail.
[0057] Example 3: High-speed rail seat back panel (1) The raw material components and addition amounts are shown in Table 5. Table 5
[0058] (2) Preparation process
[0059] The same hybrid fiber pretreatment process as in Example 1; Flame retardant preparation: Same as the flame retardant preparation process in Example 1; Functional phase dispersion: 13 parts flame retardant, 4 parts hybrid montmorillonite, 1.2 parts graphene quantum dots and 3 parts microcapsule magnesium hydroxide were added to 50 parts acetone and ultrasonically dispersed at 700W for 30 minutes to form a uniform dispersion. Matrix preparation: Mix 80 parts of E51 and 20 parts of bisphenol F epoxy resin and heat to 80°C. Add the above dispersion, 34 parts of DDS and 3 parts of CTBN. Stir mechanically for 1 hour (600 r / min), and degas under vacuum for 30 minutes (vacuum degree -0.098 MPa). The glue content is controlled at 56%. Preforming and dip coating: The mixed fibers are laid into the hollow mold and pre-pressed at 0.4MPa and 40℃ for 1 hour; a gradient dip coating process is adopted, first dipped in a low concentration mixed adhesive solution (10 parts flame retardant / 100 parts matrix) for 12 minutes, drained and then dipped in a high concentration mixed adhesive solution (13 parts flame retardant / 100 parts matrix) for 18 minutes. Gradient curing: The product is placed in an autoclave and cured according to the following procedure: 100℃ for 2 hours → heating rate 5℃ / min to 140℃ → holding for 2.5 hours → heating rate 5℃ / min to 160℃ → holding for 2 hours, curing pressure 0.9MPa, and then naturally cooled to room temperature. Wear-resistant coating spraying: Dissolve 3 parts PEEK in 20 parts NMP, stir until completely dissolved, and spray evenly onto the cured back plate surface using a spraying equipment (coating thickness 0.3mm), and dry at 180℃ for 2 hours; Post-processing: After demolding, the edges are trimmed to obtain the finished high-speed rail seat back panel (size: 800mm×500mm×10mm).
[0060] (3) Performance test results are shown in Table 6 Table 6 The above examples demonstrate that the material of the present invention achieves a three-in-one performance of "flame retardant-impact resistant-wear resistant" through the combination of high fiber content and wear-resistant coating, combined with the protective effect of dense expandable carbon layer, making it fully suitable for high-frequency use scenarios of seat back panels. Comparative Example 1: Unhybridized (Physically blended PN flame-retardant system) composite materials and their preparation This comparative example abandons the POCN hybrid design of molecular-level graft copolymerization of the present invention, and uses the traditional physical blending method of phosphorus source + nitrogen source + acid source to prepare the flame retardant system. The other raw material components, ratios, preparation process parameters and performance test conditions are completely consistent with those of Example 1 (high-speed rail side wall panel), which is used to highlight the core role of POCN molecular-level hybrid modification in flame retardancy, char formation performance and mechanical-flame retardant synergy, and to verify the technical advantages of the hybrid intumescent flame retardant of the present invention compared with the traditional physical blending system.
[0061] (1) Formula composition The hybrid reinforcement, epoxy matrix, curing and toughening system, synergistic additives, and solvents are all completely consistent with those in Example 1; The flame retardant system in this comparative example was replaced with a physical blend phosphorus-nitrogen-acid system (total addition amount 11 parts, the same as the amount of hybrid flame retardant added in Example 1), specifically DOPO-OH (5 parts) + polyphosphate ester (4 parts) + melamine-formaldehyde resin (2 parts), without molecular-level graft copolymerization reaction.
[0062] (2) Preparation process and technology ① The processes of hybrid fiber pretreatment, matrix preparation, preforming and dip coating, gradient curing, etc. are completely consistent with those in Example 1; ② Flame retardant system treatment: DOPO-OH, polyphosphate, and melamine-formaldehyde resin are directly added to acetone solvent, mixed with synergistic additives, and ultrasonically dispersed at 700 W for 30 min. There is no step-by-step graft copolymerization to prepare hybrid flame retardants. The remaining dispersion, dip coating and other processes remain unchanged.
[0063] (3) Performance test results are shown in Table 7 Table 7 Traditional physically blended PN flame retardant systems lack POCN molecular-level hybridization modification, relying solely on mechanical mixing to achieve a simple blend of phosphorus, nitrogen, and acid sources, resulting in a significant deterioration in core performance. The flame retardant has no long-lasting effect: the hybrid structure without covalent bonding, the flame retardant is only physically bonded to the matrix and fiber, the Soxhlet extraction retention rate is less than 60% after 24 hours, it is easy to migrate and precipitate, and cannot meet the long-term service requirements of high-speed rail. The char-forming performance is severely inadequate: without the ceramic coating of POC covalent chains and the synergistic char-forming regulation of acid source-gas source, the char layer formed during combustion is loose and porous, and easily collapses. The char layer thickness is only 37.7% of that of the hybrid system, resulting in a significant reduction in heat insulation and flame retardant effects. The oxygen index decreases by 11 percentage points, the flame retardant rating drops to V-2, and the heat penetration time is shortened by 56.2%. Severe mutual damage between mechanical and flame retardant properties: Physically blended flame retardant particles are prone to stress concentration, and the lack of covalent interconnection between the non-hybridized flame retardant and the matrix and fibers leads to a sharp drop in interfacial bonding strength, a 26.2% decrease in tensile strength, and a 47.7% decrease in low-temperature impact strength, completely breaking the synergistic balance between mechanical and flame retardant properties. Poor safety performance: Defects in the charcoal layer structure lead to a sharp increase in the release of smoke and toxic gases during combustion, with the smoke density level increasing by 116.7%, posing serious secondary fire hazards.
[0064] The above results fully verify that the molecular-level hybrid modification of POCN is the core design point of this invention. The covalent hybrid structure constructed by stepwise graft copolymerization achieves molecular-level dispersion and bonding of phosphorus, nitrogen, oxygen and carbon elements, fundamentally solving the industry pain points of easy migration, poor char formation and mutual performance loss in traditional physical blend PN flame retardant systems. It is the key to achieving long-lasting flame retardancy, dense char formation and synergistic improvement of mechanical and flame retardancy in materials.
[0065] Finally, it should be noted that the above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments and comparative examples, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments and comparative examples, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments and comparative examples of the present invention.
Claims
1. A method for preparing a POCN hybrid intumescent flame-retardant material, characterized in that, include: S1, a flame retardant is prepared by using a phosphorus source containing phosphorus, a nitrogen source containing nitrogen, and an acid source containing polyphosphate groups; S2, the flame retardant and resin matrix are mixed and cured to obtain a flame retardant material; S1 includes: S101, a phosphorus source and a material including epoxy groups are mixed and reacted to obtain a phosphorus-carbon reactant containing POC chains; S102, the phosphorus-carbon reactant and the acid source are mixed, and a hybrid mixture is obtained after the reaction; S103, the hybrid mixture is mixed with a nitrogen source, and a flame retardant is obtained after the reaction; The reaction temperature in S101 is 70~80℃ and the reaction time is 1.5~2.5h; the reaction temperature in S102 is 85~95℃ and the reaction time is 2.5~3.5h; the reaction temperature in S103 is 80~90℃ and the reaction time is 2.0~3.0h. In S1, the phosphorus source includes at least one DOPO derivative, which includes at least one of DOPO-OH, DOPO-MA, and DOPO-EP. In S1, the nitrogen source includes at least one of melamine-formaldehyde resin, melamine cyanurate, and dicyandiamide; In S1, the acid source includes at least one of polyphosphate ester and ammonium polyphosphate; S2 includes: The flame retardant, synergist, and resin matrix are mixed and cured to obtain a flame retardant material; wherein the synergist includes at least one of graphene-based additives, hybrid montmorillonite, microencapsulated hydroxide, and hexagonal boron nitride. The mass fractions of each substance in S2 are as follows: 8-14 parts of the flame retardant, 0.6-1.3 parts of the graphene additive, 2-4 parts of the hybrid montmorillonite, 1.7-2.3 parts of the microencapsulated hydroxide, and 90-140 parts of the resin matrix.
2. The method for preparing a POCN hybrid intumescent flame-retardant material according to claim 1, characterized in that, Before S2, it also includes: Select at least one fiber; the type of fiber includes at least one of basalt fiber, carbon fiber and glass fiber; The selected fibers were grafted and modified to obtain modified fibers. S2 includes: S201, the flame retardant, the synergistic additive and the resin matrix are mixed to obtain a mixed adhesive; S202, the modified fiber is impregnated with the mixed adhesive and cured to obtain a flame-retardant material.
3. The method for preparing a POCN hybrid intumescent flame retardant material according to claim 2, characterized in that, Before S202, the modified fiber is pre-compressed. S202 includes: The modified fiber is first dipped in a low-concentration mixed adhesive solution of 8-10 parts flame retardant / 100 parts resin matrix, drained, and then dipped in a high-concentration mixed adhesive solution of 11-13 parts flame retardant / 100 parts resin matrix. The modified fibers impregnated with the mixed adhesive solution are subjected to gradient curing.
4. The method for preparing a POCN hybrid intumescent flame retardant material according to claim 3, characterized in that, The pre-compression molding is carried out at 0.3~0.5MPa and 25~40℃.
5. The method for preparing a POCN hybrid intumescent flame retardant material according to claim 3, characterized in that, The gradient curing process has a heating rate of 3~6℃ / min, holding temperatures of 100~110℃, 130~140℃ and 150~160℃, and a curing pressure of 0.7~0.9MPa.
6. The method for preparing a POCN hybrid intumescent flame retardant material according to claim 1, characterized in that, S2 includes: The flame retardant, the synergistic additive, the resin matrix, the curing agent and the toughening agent are mixed and cured to obtain a flame retardant material; wherein the resin matrix includes at least one epoxy resin.
7. A POCN hybrid intumescent flame retardant material, characterized in that, It is prepared according to any one of claims 1-6.
Citation Information
Patent Citations
Poly-phosphate flame retardant containing DOPO side-chain structure and preparation method thereof
CN101838538A
Bio-based microencapsulated mfapp flame retardant, and preparation method therefor and use thereof
WO2023050316A1
